REPUBLIQUE DEMOCRATIQUE DU CONGO UNIVERSITE DE L’UELE - IKABU, Corneille BOGOY (IJRDO - Journal of Social Science and Humanities Research, 2018)
Although guaranteed by the Democratic Republic of the Congo’s constitution (law), the question of parity between man and woman remains theoretical. This study consists of an assessment of the woman’s political representativeness in Congolese politics institutions in order to suggest ways and means of achieving this equality provided for by the law. This study shows that women remain under-represented in politics institutions despite the apparent desire of the political authorities to promote them. By way of illustration, the woman was represented at only 15% in institutions derived respectively from the inter-Congolese held in Sun City dialogue in 2003 and the first legislature of the third republic. For this study, achieving this parity requires a strong and clear involvement of the public authorities by integrating the "gender" approach at all levels of decision-making and in all sectors of national life, but also self-appropriation by the woman herself of the issue through self-sensitization.